Análise da rede de relacionamentos em sistemas locais de inovação : a experiência de Santa Rita do Sapucaí MG - Costa Júnior, Hélio Lemes (2012)
This work focuses on the development and support of clusters of firms in a local productive arrangement, analyzing the relevance of innovation, the innovation system that companies form, along with educational institutions and support agencies, analyze business interactions between the firms and their interactions with the education institutions and support agencies, from the point of view of skilled labor employment, relations among the components of the system for training, knowledge acquisition and research and development. Beginning with the case study of the Valley of Electronics, technological pole located in Santa Rita do Sapucaí, a small town in Minas Gerais - Brazil, it was possible to conclude that, even with little commercial trade among the actors of the local productive arrangement, there is information exchange between educational institutions and businesses and there are subjective aspects that justify the continued development and maintenance of the pole for almost four decades.